Supra-subduction melt modification of the fossil subcontinental lithospheric mantle: insights from ultra-depleted Khara-Nur ophiolitic peridotites (Eastern Sayan, central Asian orogenic belt) - Gornova, Marina A.; Belyaev, Vasiliy A.; Karimov, Anas A.; Skuzovatov, Sergei Yu.; Karmanov, Nikolay S.; Medvedev, Alexander Ya.; Bryanskiy, Nikolay V. (Frontiers in Earth Science, 2023)
Mantle peridotites from the Mesoproterozoic forearc-type ophiolites in the Eastern Sayan range (Eastern Siberia) provide insights into the nature and formation processes of the supra-subduction mantle. The peridotites are represented by porphyroclastic harzburgites and dunites. The harzburgites have strongly refractory compositions recorded in high Mg# olivine (0.912-0.927) and orthopyroxene (0.916-0.935), high Cr# spinel (0.45-0.66), low Al2O3 and Cr2O3 abundances in orthopyroxene, the lack of residual clinopyroxene, low HREE abundances in orthopyroxene, clinopyroxene and wholerocks. Some rocks are relatively enriched in SiO2, which is a common feature of supra-subduction (arc and forearc) peridotites and suggests hydrous melting, whereas the rest resemble the chemistry of residues from anhydrous melting of depleted mantle (DM). The whole-rock Al2O3 and Cr-spinel compositions reflect high degrees of partial melting, which initiated in the garnet facies. The Khara-Nur peridotites experienced modification by high-Mg, low-Ti hydrous (boninitic or tholeiitic) arc melts, which crystallized newly-formed minerals (clinopyroxene, Cr-spinel, olivine) in harzburgites. The trace-element composition of clinopyroxene (YbN = 0.5-1.0, La/YbN = 0.05-0.5) resembles that of clinopyroxene from the forearc peridotites and reflects low melt/rock ratio. In dunites, melt percolation resulted in growth of Cr-spinel hosting multiphase inclusions (olivine + clinopyroxene + orthopyroxene + amphibole + phlogopite). Clinopyroxenes from Cr-spinel-hosted inclusions exhibit considerable variations in trace element composition due to heterogeneity of parental melts. Remarkably low Fe 3+ /∑Fe ratios (0.02-0.12) of Cr-spinels in both harzburgites and dunites are uncommon in SSZ mantle rocks and cannot be explained in terms of the supra-subduction processes, such as partial melting and melt percolation. The whole-rock and mineral compositions of Khara-Nur peridotites, along with previously reported Paleo-to Mesoproterozoic Re-Os model ages, suggest an This is a provisional file, not the final typeset article affinity to ultra-depleted Proterozoic subcontinental lithospheric mantle (SCLM). Overall, the Khara-Nur mantle rocks most likely represent a block of SCLM which underwent melt interaction in a supra-subduction tectonic setting that yielded boninitic and tholeiitic melts comprising now the crustal part of Eastern Sayan ophiolites.